Tectonic Subsidence in the Syrian Coastal Range During Cretaceous - عبد الكريم العبد الله (Latakia University Journal -Basic Sciences Series, 2022)
Investigation of tectonic subsidence of Cretaceous formations in the Syrian Coastal Range using three litho-stratigraphic columns, located in its northern, its southern parts and in the Lattakia-1 well, shows three stages of tectonic subsidence; during Albian, Cenomanian and Maastrichtian ages. The subsidence attained highest value in the northern Coastal Range. This study also shows the presence of an uplift stage from Coniacian to Campanian, The uplift attained highest value in the Lattakia-1 well. These stages contributed with sea level changes in sedimentation evolution of the Cretaceous basin, recorded highest value of sedimentation rate correspondent to tectonic subsidence stages. The highest value reached 45 m/My to 67 m/My during Cenomanian age. The stages recorded at studied curves in the Coastal Range are not only local, yet it affected by regional stages at the level of northern Arabian Plate. It was related to the opening of the Eastern Mediterranean in Lower Cretaceous and to the Ophiolitic Obduction and the following subsidence resultant of its loading at Upper Cretaceous.